1998
DOI: 10.1161/01.hyp.32.4.705
|View full text |Cite
|
Sign up to set email alerts
|

Nerve Growth Factor Gene Locus Explains Elevated Renal Nerve Growth Factor mRNA in Young Spontaneously Hypertensive Rats

Abstract: Abstract-Nerve growth factor (NGF) controls the growth of sympathetic nerves and is increased in young spontaneously hypertensive rats (SHR). The NGF gene has been linked genetically with hypertension in the SHR strain and may explain high NGF mRNA levels. To test for genetic linkage between the NGF gene and its expression in vivo, we examined renal NGF mRNA levels in male SHR, control Donryu rats (DRY), and F 2 rats derived from SHR and DRY at ages 2, 4, 10, and 20 weeks. Tail-cuff blood pressure was measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
1

Year Published

2000
2000
2005
2005

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 27 publications
(37 reference statements)
1
13
1
Order By: Relevance
“…Therefore, our linkage analysis is expected to provide important information with respect to narrowing the field of candidate QTLs. However, in their analysis of gene-segregating rats from a cross of SHR with normotensive Donryu rats, Harrap and co-workers suggested that the NGF gene locus of SHRs is linked to high blood pressure and increased NGF gene expression (12,13); thus, their results are in conflict with ours. At this point in time, the reason for this contradiction remains unclear.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…Therefore, our linkage analysis is expected to provide important information with respect to narrowing the field of candidate QTLs. However, in their analysis of gene-segregating rats from a cross of SHR with normotensive Donryu rats, Harrap and co-workers suggested that the NGF gene locus of SHRs is linked to high blood pressure and increased NGF gene expression (12,13); thus, their results are in conflict with ours. At this point in time, the reason for this contradiction remains unclear.…”
Section: Discussioncontrasting
confidence: 71%
“…Kapuscinski et al reported that the NGF gene locus was linked to blood pressure in genetic crosses of SHRs and normotensive Donryu rats based on a restriction fragment length polymorphism (RFLP) analysis of the NGF gene between these strains (12). Furthermore, Charchar et al reported that increased NGF gene expression also depended on the number of NGF alleles of the SHR genotype (13). These findings led us to search for mutations within the cis-element, especially in the promoter region of the NGF gene in SHRs and SHRSPs.…”
Section: Introductionmentioning
confidence: 99%
“…The development of the kidney has been extensively studied in normotensive and hypertensive rats [6][7][8][9][10][11][12][13][14]. In this species afferent renal innervation has fully developed around birth while efferent sympathetic renal innervation continues to develop from embryonic day 16 through postnatal day 21 [6].…”
Section: Development Of Renal Sympathetic Innervationmentioning
confidence: 99%
“…Further biochemical polymorphic analysis revealed no differences between the profiles of the purported DRY from Melbourne and reference F344. Other studies in Japan by Dr Tanase confirmed that the polymorphism profiles of 43 markers from chromosomes 1, 2,4,5,6,7,8,9,10,12,14,16,17,18,19,20, and X were completely consistent between the purported Donryu animals from Tokyo and known authentic F344 rats from Sankyo.In addition, the DNA polymorphic profile of a previous cross derived from SHR and authentic DRY animals was compared against the profile of the purported DRY from Tokyo. Of the 43 markers tested, the comparisons were informative for 17 loci, for which the cross (derived from authentic DRY) and the purported DRY animals were identical at 7 and nonidentical at 10.…”
mentioning
confidence: 73%